Reed Smoot papers - Smoot, Reed, 1862-1941.
Chiefly correspondence of Smoot and others together with senate reports and documents relating to bimetallism, excise tax, farm expenditures, imports, prices, and other national economic and political matters. Correspondents include Charles L. Abernethy, Harry A. Austin, David N. Blair, A. D. Bright, Edward N. Dingley, John Hay, John B. Jackson, Justin S. Morrill, C. R. Nash, Richard Olney, John Sherman, and William M. Stewart
In part, handwritten and typewritten transcripts.
Businessman, Mormon religious leader, and U.S. senator from Utah.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Abernethy, Charles L. -- 1872-1955 -- Correspondence; Austin, Harry A. -- Correspondence; Blair, David N. -- Correspondence; Bright, A. D. -- Correspondence; Dingley, Edward N. -- 1862-1930 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Jackson, John B. -- 1862-1920 -- Correspondence; Morrill, Justin S. -- 1810-1898 -- Correspondence; Nash, C. R; Olney, Richard, -- 1835-1917 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; Stewart, William M. -- 1827-1909 -- Correspondence; Agriculture -- Economic aspects -- United States; Bimetallism; Excise tax; Imports; Prices; Utah -- Politics and government; United States -- Appropriations and expenditures; United States -- Economic conditions; United States -- Politics and government; Businessmen; Religious leaders; Senators, U.S. -- Utah